2013
DOI: 10.1155/2013/597845
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Asthma and Declared Asthma in Poland on the Basis of ECAP Survey Using Correspondence Analysis

Abstract: Results of epidemiological and public health surveys are often presented in the form of cross-classification tables. It is sometimes difficult to analyze data described in this way and to understand relations between variables. Graphical methods such as correspondence analysis are more convenient and useful. Our paper describes an application of correspondence analysis to epidemiological research. We apply the basic concepts of correspondence analysis like profiles, chi-square distance to medical data concerni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
1
5
0
3
Order By: Relevance
“…Regional prevalence of AB was also studied in Poland. This study showed differences in occurrence of AB among regions (Zalewska et al, 2013). Our current study has similar conclusions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Regional prevalence of AB was also studied in Poland. This study showed differences in occurrence of AB among regions (Zalewska et al, 2013). Our current study has similar conclusions.…”
Section: Discussionsupporting
confidence: 89%
“…Prevalence of AB is constantly increasing, even if this trend is different in individual countries (Accordini et al, 2013;Bahadori et al, 2009;Litonjua and Weiss, 2007;D'Amato et al, 2015;Doz et al, 2013;Gudelj et al, 2012;Kim et al, 2013;Wong et al, 2013;Zalewska et al, 2013). Numerous inductors are considered to be responsible for an increase in AB prevalence, among others it is urbanization and environmental pollution, but also more precise diagnostic and registration (Anderson et al, 2012;Bonds and Midoro-Horiuti, 2013;Daghri-Al et al, 2013;D'Amato et al, 2015;Lamnisos et al, 2013;Patel et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of asthma diagnosis reported by the subjects is slightly higher than that reported by the subjects of the ECAP survey in Małopolska [16] but closer to a survey including analysis of the results by a physician (7.6% [6.0-9.1%]) [17]. Small differences result probably from different age ranges of the populations surveyed.…”
Section: Discussionmentioning
confidence: 66%
“…Istotne zróżnicowanie częstości występowania chorób alergicznych ze względu na region i pochodzenie etniczne jest zjawiskiem dobrze udokumentowanych. W Polsce blisko 40% populacji choruje na alergie, w tym na ANN 25%, na astmę -5%, a objawy astmy ma blisko 12% ogółu badanych [9][10][11][12][13]. Średnio 1-40% przypadków ANN dotyczy alergii na pyłki roślin, natomiast 1-13% przypadków wiąże się z występowaniem przewlekłego ANN [9].…”
Section: Występowanieunclassified